Barriers and facilitators adolescent females living with HIV face in accessing contraceptive services: a qualitative assessment of providers' perceptions in western Kenya. Issue 1 (18th September 2015) - Hagey, Jill M; Akama, Eliud; Ayieko, James; Bukusi, Elizabeth A; Cohen, Craig R; Patel, Rena C
Abstract : Introduction: Avoiding unintended pregnancies is important for the health of adolescents living with HIV and has the additional benefit of preventing potential vertical HIV transmission. Health facility providers represent an untapped resource in understanding the barriers and facilitators adolescents living with HIV face when accessing contraception. By understanding these barriers and facilitators to contraceptive use among adolescent females living with HIV, this study aimed to understand how best to promote contraception within this marginalized population. Methods: We conducted structured in‐depth interviews with 40 providers at 21 Family AIDS Care & Education Services ‐ supported clinics in Homabay, Kisumu and Migori counties in western Kenya from July to August 2014. Our interview guide explored the providers' perspectives on contraceptive service provision to adolescent females living with HIV with the following specific domains: contraception screening and counselling, service provision, commodity security and clinic structure. Transcripts from the interviews were analyzed using inductive content analysis. Results: According to providers, interpersonal factors dominated the barriers adolescent females living with HIV face in accessing contraception. Providers felt that adolescent females fear disclosing their sexual activity to parents, peers and providers, because of repercussions of perceived promiscuity. Furthermore, providers mentioned that adolescents find seeking contraceptive services without a male partner challenging, because some providers and community members view adolescents unaccompanied by their partners as not being serious about their relationships or having multiple concurrent relationships. On the other hand, providers noted that institutional factors best facilitated contraception for these adolescents. Integration of contraception and HIV care allows easier access to contraceptives by removing the stigma of coming to a clinic solely for contraceptive services. Youth‐friendly services, including serving youth on days separate from adults, also create a more comfortable setting for adolescents seeking contraceptive services. Conclusions: Providers at these facilities identified attitudes of equating seeking contraceptive services with promiscuity by parents, peers and providers as barriers preventing adolescent females living with HIV from accessing contraceptive services. Health facilities should provide services for adolescent females in a youth‐friendly manner and integrate HIV and contraceptive services.